A Mechatronic Approach to Control of 6 DOF Parallel Manipulator - Rosario, J. M. (2019)
This paper presents a practical implementation, using reconfigurable computing applied to robotic problems. Through the proposal a hierarchical architecture, distributing the several control actions in growing levels of complexity and using resources of reconfigurable computing is possible to take into account the easiness of future modifications, updates and improvements in the robotic applications. A practical example is presenting using reconfigurable computing, of Stewart- Gough platform control, where the developed software and hardware are structured in independent blocks, through open architecture implementation, allowing the easy expansion of the system, better adapting the platform to the tasks associated to it. This open architecture implementation allows an easy expansion of the system and a better adaptation of the platform to its related tasks.